2021
DOI: 10.1096/fba.2020-00123
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of 2018–2020 research on NCDs and physical activity in Ghana: Groundwork for a monitoring system and action plan

Abstract: Background Physical inactivity is a risk factor for chronic noncommunicable diseases (NCDs), yet national surveillance of physical activity (PA) levels is not well defined. Though Ghana has a national health policy that emphasizes health promotion and prevention of lifestyle diseases, and an NCD policy with PA recommendations in 2012, it does not have an integrated plan of action to address widespread physical inactivity. Objective This review aims to identify the nature and extent of research in NCDs and PA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…This can be achieved by developing collaborative guidelines or protocols that outline the appropriate indications for referral to clinical exercise physiologists [ 43 ], as well as implementing integrated care models [ 44 ] where doctors and clinical physiologists work within the same healthcare setting. Consistent with previous research findings [ 30 , 31 ], this study also revealed that doctors face time constraints, mainly due to a high volume of patients, which limits their ability to discuss PA during patient consultation. There is, therefore, the need for a collaborative effort, given that a collaborative team has a significant influence on behaviour change for patients with chronic diseases including T2DM [ 45 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This can be achieved by developing collaborative guidelines or protocols that outline the appropriate indications for referral to clinical exercise physiologists [ 43 ], as well as implementing integrated care models [ 44 ] where doctors and clinical physiologists work within the same healthcare setting. Consistent with previous research findings [ 30 , 31 ], this study also revealed that doctors face time constraints, mainly due to a high volume of patients, which limits their ability to discuss PA during patient consultation. There is, therefore, the need for a collaborative effort, given that a collaborative team has a significant influence on behaviour change for patients with chronic diseases including T2DM [ 45 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, facilitators of PA participation identified were perceived health benefits, physician/family support, and access to community or faith-based fitness groups [ 30 ]. Furthermore, a scoping review focusing on non-communicable diseases and PA in Ghana revealed significant PA barriers and facilitators in Ghanaian adults [ 31 ]. The review identified barriers including limited knowledge and access to facilities, absence of suitable exercise spaces, and insufficient knowledge of PA guidelines and implementation methods [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reviews conducted so far on HTN in Ghana have focused on its prevalence and associated factors [15,27] as well as impact of physical activity [28]. These limited reviews failed to adduce evidence on Ghana's policies response towards HTN control.…”
Section: Introductionmentioning
confidence: 99%